The Effect of Learning Models and Learning Styles on Social Science Learning Outcomes of Arrahman Percut Students - Lili Nur Indah Sari; Abdul Muin Sibuea; Samsidar Tanjung (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims (1) to determine the differences in social studies learning outcomes taught by the Two Stay Two Stray (TSTS) learning model which is higher than the social studies learning outcomes with the Problem Based Learning model. (2) To find out the differences in social studies learning outcomes of students who have a higher visual learning style than the social studies learning outcomes of students who have a kinesthetic learning style. (3) To determine the interaction between learning models and student learning styles in influencing the social studies learning outcomes of private students, Ar Rahman Percut. The population of this study was 122 students of class VII-A and VII-B of Ar Rahman Percut Private Middle School. Samples were taken by cluster rondom sampling. The sample used in this study was 63 students. The selected sample is classVII-A and class VII-B. The instrument used was a multiple choice test, amounting to 30 items and a learning style questionnaire. The data were analyzed at the significant level = 0.05, followed by the Scheffe further test after the normality and homogeneity tests. The results showed that, (1) There are differences in social studies learning outcomes, where the social studies learning outcomes with the Two Stay Two Stray (TSTS) learning model are higher than the social studies learning outcomes with the Problem Based Learning model with Fcount 8,70> Ftable 4.00, (2) There are differences in student social studies learning outcomes, where the social studies learning outcomes of students who have a visual learning style from the social studies learning outcomes of students who have a kinesthetic learning style with Fcount 5.01> Ftable 4.00, (3) There is an interaction between the learning model and the learning style of the students' social studies learning outcomes Fcount 5.20> Ftable 4.00